EGD for Refractory Toxidromes: Is It Time to Add to the Algorithm?. (June 2022) - Allen, Kelsey; Kane, Ian; Connors, Nicholas; Tecklenburg, Frederick; Marvin, Whitney
Toxic ingestions are an increasing concern among pediatric patients in the United States. Less common, but troubling, are those patients with persistent toxicity symptoms despite stabilization, resuscitative, and decontamination efforts. We report a case of refractory serotonin toxicity in an adolescent for whom endoscopic removal of medication remnants led to the resolution of his clinical course. A 14-year-old male patient with anxiety and depression, treated with escitalopram and clonidine, presented to an outside hospital (OSH) emergency department (ED) with tonic-clonic seizure activity and altered mental status. Non-contrast head computed tomography (CT), complete blood count, and basic metabolic panel were unrevealing. Repeated seizure activity that occurred in the OSH ED prompted transfer to a tertiary pediatric care facility for ongoing management. Based on the constellation of symptoms (tachycardia, muscle rigidity, and lower extremity clonus) and his medication history, there was concern for serotonin toxicity. His clinical course worsened, despite treatment with midazolam and cyproheptadine, requiring intubation for respiratory failure. Because of his refractory symptoms and concern for ongoing medication side effects, on hospital day 4, he underwent an esophagogastroduodenoscopy (EGD), which revealed 20 partially digested pills firmly adhered to the gastric mucosa. The pill fragments were removed and whole bowel irrigation was started, and the patient improved rapidly, allowing for extubation within 24 hours. An EGD is not routinely used for the management of toxic ingestions. In addition to this case, evidence from prior case reports supports the judicious use of EGD as a diagnostic and therapeutic decontamination modality for severe toxicities.